Molecular Resonance Imaging of the CAIX Expression in Mouse Mammary Adenocarcinoma Cells - Claudia Quattrociocchi; Alberto Mangia; Silvio Aime; Valeria Menchise; Daniela Delli Castelli (MDPI AG, 2023)
The carbonic anhydrase isoform IX (hCAIX) is one of the main players in extracellular tumor pH regulation, and it is known to be overexpressed in breast cancer and other common tumors. hCA IX supports the growth and survival of tumor cells, and its expression is correlated with metastasis and resistance to therapies, making it an interesting biomarker for diagnosis and therapy. The aim of this work deals with the development of an MRI imaging probe able to target the extracellular non-catalytic proteoglycan-like (PG) domain of CAIX. For this purpose, a specific nanoprobe, LIP_PepC, was designed by conjugating a peptidic interactor of the PG domain on the surface of a liposome loaded with Gd-bearing contrast agents. A Mouse Mammary Adenocarcinoma Cell Line (TS/A) was chosen as an in vitro breast cancer model to test the developed probe. MRI results showed a high selectivity and sensitivity of the imaging probe toward hCAI-expressing TS/A cells. This approach appears highly promising for the in vivo translation of a diagnostic procedure based on the targeting of hCA IX enzyme expression.